Simulation of un industrial waste treatment tank (Research, Society and Development, 2020)
The objective of the present work was to evaluate the operation of an industrial sedimentation tank used in the separation of solid waste from the petrochemical industry. The depth data were obtained through a “interface float”, while the diameters and the positions of the particles through the CFD simulation. The computational fluid dynamics simulator (FLUENT 6.3.26) was used to perform a multiphase simulation using the Euler-Lagrange approach and was used to determine the particles trajectories and cotours of solids accumulated in the bottom of the tank. This allowed a better understanding of solids accumulation and improvement of the cleaning process. In the simulation of the tank a large computational mesh comprising 464,094 computational nodes was designed. The use of the Euler-Lagrange approach meant that a discrete phase model had to be established and the parameters of Rosin-Rammler solids distribtion model for the boundary conditions of the simulation had to be determined.